Assessment of phytochemicals, antimicrobial, antioxidant and cytotoxicity activity of methanolic extract of Tinospora cordifolia (Gurjo) - Shrestha, Tara; Lamichhane, Janardan (Nepal Journal of Biotechnology, 2021)
Traditionally used medicinal plants are the major resources of biologically active metabolites which are widely used for the cure of numerous diseases especially in developing countries where health facilities are rare. Many plants are in use for centuries but there is not enough scientific evidence and exploration. This research is focused on phytochemicals, antibacterial, antioxidant and cytotoxicity activity analysis of one of the most commonly used ethnomedicine Tinospora cordifolia collected from the Kavrepalanchok district of Nepal. Phytochemicals analysis of methanol extract of T. cordifolia showed the presence of alkaloids, coumarin saponins, glycosides, reducing sugar, and triterpenes. Antibacterial activity performed by disc diffusion method exhibited the highest activity against Streptococcus with a zone of inhibition are 10.3mm, 8.5mm, 6.5mm, and 6mm at 200mg/ml, 100mg/ml, 50mg/ml, and 25mg/ml of concentration respectively. DPPH radical scavenging activity increased with increasing concentration of extract. When compared with ascorbic acid at equivalent concentration, the extract shows a lower scavenging profile (56.07% for the extract and 98.01% for ascorbic acid at 320 ppm). Cytotoxicity was evaluated in terms of LC50 (lethality concentration). The result showed that the extract of T. cordifolia was found to be toxic with an LC50 value of 232.64μg/ml. The bioactive component present in the plants could be the result of its pharmacological effects that support the traditional use of plants.